Implementation Effectsgreen Accounting on Company Value with Disclosurecorporate Social Responsibility as a Mediation Variable - Ni Wayan Sri Kesuma Dewi; I Wayan Suartana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to test and provide empirical evidence regarding the effect of green accounting on firm value both directly and indirectly through the disclosure of corporate social responsibility as a mediating variable. This research was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The sample was determined using purposive sampling method, with a total of 17 companies for three years of observation, so that 51 observation data were obtained. The data analysis technique used is path analysis and sobel test. The results showed that green accounting has a positive and significant effect on corporate social responsibility disclosure, green accounting and corporate social responsibility disclosure have no significant effect on firm value, and the results of the sobel test state that corporate social responsibility disclosure is unable to mediate the relationship between green accounting and firm value.